On the design of fully symmetrical bridge-style circuits. Issue 3 (3rd May 2016) - Faghih Mirzaee, Reza; Jasemi, Masoomeh; Valizadeh, Ali; Bagherzadeh, Nader
ABSTRACT: This paper deals with the bridge-style circuits. They are highly efficient in terms of transistor density per unit of area. They comply with the conventional CMOS style and form a full-swing and robust structure. First, we clarify the necessary conditions under which a Boolean function can be implemented fully symmetrical. Then, it is demonstrated that it is possible to design out of functions fully symmetrical. Eventually, we show how the pull-up and pull-down networks are constructed in a bridge circuit for any three-input function which fulfils the conditions of being implemented fully symmetrical.